"Barrier-Free Environment" In Inclusive Education And Possibilities Of Its Formation (Diversity Research: Journal of Analysis and Trends, 2023)
This article discusses the socio-pedagogical problems that impede the implementation of inclusive education in society, teacher education within the framework of the innovation cluster (IPEC) to meet the educational needs of students with disabilities, as well as to increase their participation in the pedagogical process. The concept of "barrier-free environment" is analyzed. and pedagogical conditions.